Study on plugging law and plugging removal effect of pre filled screen in natural gas hydrate argillaceous silt reservoir - Haoxian Shi; Jiudong Shi; Weigang Du; Fulong Ning; Wenwei Xie; Ranli Zhang; Yanjiang Yu (PLoS ONE, 2026)
To address the issue of production decline caused by natural gas hydrate blockage in offshore screen pipes, optimization experiments for high-efficiency rotary water jet backflushing technology were conducted. The outer pressure and permeability of the screen pipes were used as criteria to assess backflushing effectiveness. The study examined the effects of various factors, including the type of backflush tool, tool movement speed, screen pipe type, and the presence of perforated pipes. The results revealed that, compared to high-pressure and low-pressure rotary spray guns, the high-pressure cavitation jet rotary flushing tool provided the best backflush performance. Backflushing effectiveness was higher at a tool movement speed of 1 m/min than at 2 m/min. Additionally, 30/40 mesh screen pipes demonstrated significantly better backflush performance than 40/70 mesh pipes. Screen pipes with perforated pipes showed lower backflush effectiveness compared to those without. These findings offer valuable insights for optimizing the backflushing process of offshore natural gas hydrate screen pipes.